Prevalence of Oral Impacts as Daily Performances among Adult Dental Patients in a Nigerian Tertiary Hospital - B.E. Edetanlen; K.M. Ezigbo (Nigerian Dental Journal)
Background: Oral conditions do not only cause pain but affect the various aspects of individual's daily performances. Objective: To investigate the prevalence of oral health impact on daily performance in adult patients at a Southern Nigerian tertiary hospital. Patients and Methods: A cross-sectional study was conducted on dental patients that attended the University of Benin Teaching Hospital, Benin-City, Nigeria. Oral Impacts on Daily Performance (OIDP) questionnaire was used to evaluate the impact of oral health status on the daily performance. The data collected were analysed with descriptive and inferential statistics. P-value less than 0.05 was considered statistically significant. Results: A total of 110 patients (43 males and 67 females) participated in the study. The age range of the participants was 18-70 years and the mean age of the participants was 31.8±12.8 years. The mean ODIP score of the study participants was 1.58 ±2.77 with a range of 0 to 14. Sixty percent of all subjects had at least one daily performance affected by an oral impact in the previous six months. The ODIP indicators most commonly affected by oral health status were eating and enjoying food (31.8%), smiling and showing teeth (13.6%), and enjoying social contact with people (10.9%) and cleaning teeth (10.0%), The least commonly affected were maintaining usual emotional status (9.1%), sleeping and relaxing (9.1%), carrying out daily school task (8.20%), and speaking and pronouncing words clearly (7.30%).There were no statistically significant difference between ODIP score and age, gender, place of residence, level of education and oral/dental conditions. Conclusion: Oral health had an impact on daily performances of adult dental patients in southern Nigeria. The daily activities mostly affected was eating and enjoying food.